Kelang port authority materials handling of general cargo in quay transfer operation in north port of port Kelang / Zet Hanafiah Haron - Haron, Zet Hanafiah (Faculty of Business and Management, 1987)
The important of materials handling has been realised by port authorities so that fast and efficient service can be provided in handling the cargoes. It is a vital aspect in physical distribution as it contributes to the distribution process. Handling of the cargoes need mechanical handling equipments rather using human and horse-driven cart which are slow and time consuming. So as to achieve high productivity, these handling equipments must be efficient in performing their tasks. A research study should be conducted in order to find out the reliability of the present equipment operated by the Kelang Port Authority. The total down time and utilisation of the equipments represent the rate of work being performed. These 2 factors clearly indicate the equipments' performance and, thus, the research study being carried out should emphasize more on these 2 areas.